ISLAMIC FINANCIAL LITERACY AND INCLUSION LEVEL - Nevi Hasnita; Putri Nazirah; Muksal, Muksal (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2023)
ISLAMIC FINANCIAL LITERACY AND INCLUSION LEVEL Abstract Purpose: This study aims to assess the level of literacy and inclusion of Islamic finance in the city of Banda Aceh following the implementation of Qanun No. 11 of 2018 on Islamic Financial Institutions. The research seeks to contribute insights into the impact of regulatory measures on financial literacy and inclusion in a region with a specific focus on Islamic finance. Design/methodology/approach: A descriptive qualitative method employing a questionnaire was used to gather data for this study. The research analyzed the responses to evaluate the changes in Islamic financial literacy and inclusion among the residents of Banda Aceh. Findings: The results indicate a notable increase in Islamic financial literacy from 71.99% to 89.70%, accompanied by an Islamic financial inclusion rate of 83.4%. Categorizing these results according to Chen and Volpe's criteria, the Islamic financial literacy and inclusion in Banda Aceh City fall into the high category. The findings underscore the positive impact of Qanun No. 11 of 2018, suggesting an enhanced understanding of Islamic financial concepts among the residents. Research limitations/implications: While the study provides valuable insights, it is essential to acknowledge some limitations. The research focuses on a specific geographic location, and the results may not be generalizable to other regions. Additionally, the study relies on self-reported data, which may be subject to respondent bias. Practical implications: The findings of this study emphasize the importance of improving Islamic financial literacy. Residents of Banda Aceh City are encouraged to enhance their knowledge of various financial topics, including budgeting, investing, credit, insurance, and retirement planning. Increased financial literacy can empower individuals to make more informed decisions when utilizing services and products offered by financial institutions. Keywords: Literacy; inclusion, Islamic Finance TINGKAT LITERASI DAN INKLUSI KEUANGAN SYARIAH Abstrak Tujuan: Penelitian ini bertujuan untuk mengkaji tingkat literasi dan inklusi keuangan syariah di Kota Banda Aceh pasca penerapan Qanun No. 11 Tahun 2018 tentang Lembaga Keuangan Syariah. Penelitian ini bertujuan untuk menyumbangkan wawasan tentang dampak langkah-langkah pengaturan terhadap literasi dan inklusi keuangan di suatu wilayah dengan fokus khusus pada keuangan Islam. Desain / metodologi / pendekatan: Metode kualitatif deskriptif menggunakan kuesioner digunakan untuk mengumpulkan data untuk penelitian ini. Penelitian ini menganalisis tanggapan untuk mengevaluasi perubahan literasi dan inklusi keuangan Islam di antara penduduk Banda Aceh. Kesimpulan: Hasilnya menunjukkan peningkatan literasi keuangan syariah yang signifikan dari 71,99% menjadi 89,70%, disertai dengan tingkat inklusi keuangan syariah sebesar 83,4%. Mengkategorikan hasil ini sesuai dengan kriteria Chen dan Volpe, literasi dan inklusi keuangan syariah di Kota Banda Aceh termasuk dalam kategori tinggi. Temuan ini menggarisbawahi dampak positif Qanun No. 11 tahun 2018, menunjukkan peningkatan pemahaman tentang konsep keuangan syariah di kalangan warga. Keterbatasan / implikasi penelitian: Meskipun penelitian ini memberikan wawasan yang berharga, penting untuk mengakui beberapa keterbatasan. Penelitian ini berfokus pada lokasi geografis tertentu, dan hasilnya mungkin tidak dapat digeneralisasikan ke wilayah lain. Selain itu, penelitian ini bergantung pada data yang dilaporkan sendiri, yang mungkin tunduk pada bias responden. Implikasi praktis: Temuan penelitian ini menekankan pentingnya meningkatkan literasi keuangan syariah. Warga Kota Banda Aceh didorong untuk meningkatkan pengetahuan mereka tentang berbagai topik keuangan, termasuk penganggaran, investasi, kredit, asuransi, dan perencanaan pensiun. Peningkatan literasi keuangan dapat memberdayakan individu untuk membuat keputusan yang lebih tepat ketika memanfaatkan layanan dan produk yang ditawarkan oleh lembaga keuangan. Kata kunci: Literasi; inklusi, Keuangan Islam